Network algebraization and port relationship for power‐electronic‐dominated power systems - Rui Ma; Xiaowen Yang; Meng Zhan (IET Renewable Power Generation)
Abstract In the classical differential‐algebraic equations (DAEs) framework for the traditional power system stability analysis, synchronous generators are depicted by differential equations and network by algebraic equations under the quasi‐steady‐state assumption. Differently, in the power‐electronic‐dominated power system (PEDPS), the dynamics of transmission lines of network for fully differential equations should be considered, due to the rapid response of converters' controls, for example, the alternating current controls. This poses a great challenge for the cognition, modeling, and analysis of the PEDPS. In this article, a nonlinear DAE model framework for the PEDPS is established with differential equations for the source nodes and algebraic equations for the dynamical electrical network, by generalizing the application scenarios of Kron reduction. The internal and terminal voltages of source nodes of converters are chosen as ports of nodes and network. Namely, the internal and terminal voltages of source nodes work as their output and input, respectively, whereas they work as the input and output of the algebraic network, respectively. The impact of dynamical network becomes clear, namely, it serves as a (linear) voltage divider and generates the terminal voltage based on the internal voltage of the sources simultaneously. By keeping only useful independent state variables, all differential equations for the transmission lines can be transferred to algebraic equations. With this simple model, the roles of both nodes and network become apparent, and it enhances the understanding of the PEDPS dynamics. On the other hand, broad simulations are conducted and compared to verify the proposed DAE framework for the PEDPS. As all independent variables have been kept in the model, it is found that they show the same computational accuracy, but better efficiency in computational time, compared to the electromagnetic‐transient simulation results.